Constructing a lower-bound estimate of the global number of insect species on a hyperdiverse empirical foundation - Robert K. Colwell; Laura Melissa Guzman; Dirk Steinke; Anne Chao; Daniel H. Janzen; Winnie Hallwachs; Austin Baker; José L. Fernández-Triana; Paul D. N. Hebert; Frank Joyce; Robert Puschendorf; Donald L. J. Quicke; et al. (Proceedings of the National Academy of Sciences, 2026)
Estimating the number of insect species on Earth is a daunting challenge. The current consensus estimate—about six million species—is likely far too low, as we will show. Our estimate of the global number of insect species rests on a sample of more than 1,600,000 DNA-barcoded insect specimens representing 53,945 species from 15 “core” Malaise traps deployed in dry forest, cloud forest, and rainforest ecosystems of the Área de Conservación Guanacaste (ACG) in Costa Rica. Even this massive sample fails to reveal the full extent of ACG insect species richness. To estimate total ACG insect richness, we adjust the observed count of insect species by an “undersampling ratio,” computed for a hyperdiverse subfamily of parasitoid wasps (Braconidae: Microgastrinae). The ratio compares microgastrine richness from the core Malaise traps to a lower-bound estimate of true microgastrine richness—including undetected species—based on 21,669 specimens from three sources: the 15 core Malaise traps, 15 “peripheral” Malaise traps spanning all three ecosystems, and 11,373 DNA-barcoded specimens reared from some 1,500 species of microgastrine-parasitized caterpillars (Lepidoptera). To estimate global insect richness, we apply Earth/ACG ratios for tree species and several animal taxa to upscale our estimate of ACG insect richness (nearly 333,000 species). Adopting conservative assumptions, we reach an estimate of 14 to 20 million insect species on Earth, depending on the upscaling group—two to three times the current consensus estimates. Upscaling instead from a point estimate of ACG richness with a wide CI, global estimates reach nearly 30 million species.